Sharing the Nile Egypt, Ethiopia and the geo-politics of water - Milas, Seifulaziz Leo (Pluto Press, 2013)
"The Nile is widely regarded as the longest river in the world and has played a crucial role in the development of both agriculture and industry in the Horn of Africa, particularly Egypt. In Sharing the Nile, Seifulaziz Milas draws on decades of experience in the region to reveal the politics of the "Great River," and the long-standing dispute between Egypt and the upstream countries over control of its waters. Milas challenges the myth that any attempt by those countries to use this resource in their own interests, without Egypt's permission, would inevitably lead to war. The book examines Cairo's interest in Ethiopia's Blue Nile, the main source of Egypt's water supply. It recounts the history of the dispute, and describes the impact of successive Egyptian regimes' policies toward Ethiopia. Finally, Milas suggests a way forward, based on co-operation, peace, and development."--Back cover